(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Imagine that you own a time machine and have travelled back to those days when your great grandparents were children. The lifestyle of those people was physically very active and vigorous. The main activity was running, throwing and jumping for survival i.e. a man was running for search of food, safety and arranges basic needs of life. With the passes of time Kingship introduced the military and war training for supremacy, to prepare their army for war and other battles. Later on in the present era it has transformed to individual fitness, wellness and good health. In this context, the Indian Government has focused on citizen’s health by introducing various programmer of physical training, physical assessment under physical education programmer as well as has introduced celebration of International Day of Yoga, i.e. 21st June every year. In this lesson you will learn meaning and importance of physical education and yoga and its historical development in details.